Perancangan Mesin Balancing Dinamis pada Putaran Maksimal 1485 RPM dengan Metode 4 Massa Coba - Imron Fahreza Yudha; Murni Murni (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
Unbalance is defined as the condition that exists in the rotor when a vibratory force or motion is exerted on its bearings as a result of centrifugal force. Balancing is the treatment of unbalanced components by providing another centrifugal force that will oppose the original centrifugal force or by eliminating the force. Balancing process aims to reduce vibrations that occur in the rotor system by adding or reducing mass in the rotor. To determine the state of unbalance, a vibration meter is used to measure the value of vibrations that occur in unbalanced test objects.The dynamic balancing machine is designed on a laboratory scale as a support for the lecture process related to testing the balance of objects that work in rotation on the Mechanical Design Engineering S.Tr campus. In the design and construction of this dynamic balancing test tool, the design was carried out using SolidWorks software with a motor power of 1 hp with a maximum rotational speed of 1485 RPM and using a fixed shaft mounted on a test object with 2 hole disks for placement of the test mass.In the test, the 4 dynamic trial mass method was used, with the condition of the disk object being an unbalance mass of 10 grams with a different position in the two planes. This increase in mass causes the object to experience dynamic imbalance, and the vibration value becomes higher than the initial state of the machine. Then a balancing calculation was carried out, the balancing mass value for the left rotor was 5.278 g at position 00 and 13.17 g at position 2700 , while on the right rotor a counterweight mass was 0.17 g at position 00 and 2.44 g at position position 2700. After the balancing mass is installed, the results of the decrease in vibration value due to the addition of mass are 74% on the left bearing and 88% on the right bearing. In this test, the rotor was tested at several rotational speeds and all of them showed a decrease in the vibration value.